Application of Cobit Freamwork 4.1 Method in Information Technology Audit - Alya Rizki (Journal of Computer Scine and Information Technology, 2022)
To Fine the performance of information technology that can easily make decisions, so that the performance of the technology used is more effective and efficient, it is necessary to carry out an information technology audit at the BPKAD office. In this study, the standard used is COBIT 4.1, Using the calculation of the Maturity Level which represents the level of technology alignment information and objectives of the Agency. The calculation of the Maturity Level value will be carried out in the Acquire and Implement (AI2, AI3, AI4, AI5) and Deliver and Support (DS7, DS10, DS12, DS13) domains. The BPKAD office already uses information technology in every process of its activities. The overall results in the agency reached level 4 (Managed). From the level results obtained, recommendations were made that could be applied by the BPKAD office to reach the desired level, namely level 5 (Optimized) so that it could support the performance of the agency to be even better in terms of information technology